Zaangażowanie Polski w misje wojskowe Unii Europejskiej w Afryce w drugiej dekadzie XXI wieku - Lasoń, Marcin (Rocznik Integracji Europejskiej, 2015)
This paper is dedicated to the involvement of Poland in the European Union’s military operations in Africa in the 2010s. The development of military capabilities is not one of the European Union’s priorities. Nevertheless, the EU is an active participant of the international communities’ efforts to aid African states, including the use of armed forces. The vast majority of such EU missions have been undertaken in Africa. Despite the fact that this region is not a priority of Poland’s foreign and security policies, Poland has actively participated in such actions, primarily due to the peculiarities of contemporary security threats and Poland’s approach to the process of European integration. However, after initial experiences, Poland limited its involvement, due to the limited impact on the achievement of national objectives related to the EU Common Security and Defence Policy. This has been reflected in both official documents and political practice associated with deploying troops on foreign soil. The author sets forth a thesis that these limitations are too substantial, and that there are reasons for greater Polish involvement in the European Union’s military missions.